BLOCKCHAIN APPLICATION: INDONESIAN COMPETITION LAW’S PERSPECTIVES - Stevi Milenia; Tresnawati Tresnawati (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
Having advantages of consensus mechanism in decentralizing data transaction which potentially eliminates the need for third-party intermediaries, blockchain has the potential to revolutionize markets industry to decrease the showcase control of today’s centralized stages by utilizing the internet. Blockchain has been rising innovation in Indonesia, demonstrated by establishment of Indonesia Blockchain Association. Though its application in Indonesia is still restricted to cryptocurrency sector, no question that blockchains will be connected broadly in near future, and unquestionably will influence business competition. Law and technology ought to be thought of as allies-not enemies-as they feature complementary strengths, yet it might also have their curses. Some intriguing articles has even questioned how blockchain would cause the death of anti-trust, the so-called competition law. Meanwhile this article would focus on elaborating consequences of blockchain technology both positive and negative sides in Indonesia Competition Law Perspective, both in substantial and procedural law, using library research, statute, comparative, and conceptual approach.